Evaluation of allergenic properties and immunotoxicity of Homeovox - L. P. Kovalenko; E. A. Ivanova; A. S. Lapickaya; K. V. Korzhova; R. V. Zhurikov (LLC "Publisher OKI", 2020)
Homeovox, a multicomponent homeopathic treatment for laryngitis of various etiologies, was tested for allergenic properties and immunotoxicity.Methods. 80 male albino guinea pigs and 180 male СВА, C57BL/6 and F1 hybrid (CBAхС57BL/6) mice were used in the study. In order to assess immunotoxicity, Homeovox was administrated orally to mice for 14 days at doses of 100 mg/kg and 1 000 mg/kg. To assess the allergenic properties of Homeovox, albino guinea pigs were also given the drug at doses of 100 mg/kg and 1 000 mg/kg according to the standard immunization schedules.Results. Oral administration of Homeovox to mice for 14 days at doses of 100 mg/kg and 1 000 mg/kg did not cause significant changes in the main characteristics of immune response compared to controls. When assessing allergenicity, Homeovox at doses 100 mg/kg and 1 000 mg/kg administered according to the standard immunization schedules did not induce systemic anaphylaxis or active skin anaphylaxis in albino guinea pigs. The immunization of guinea pigs by Homeovox at the same doses in a mixture with Freund's complete adjuvant caused no delayed allergic reactions. Homeovox at a single oral dose of 1 000 mg/kg significantly decreased concanavalin A-induced inflammation in CBA mice by 58.4 %.Conclusion. Within the dosage range investigated, Homeovox does not induce immunotoxicity, immediate- or delayed-type allergic or pseudoallergic reactions.